Systems and frameworks for computational morphology : Third International Workshop, SFCM 2013, Berlin, Germany, September 6, 2013 Proceedings - Piotrowski, Michael; Mahlow, Cerstin (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the Third International Workshop on Systems and Frameworks for Computational Morphology, SFCM 2013, held in Berlin, in September 2013. The 7 full papers were carefully reviewed and selected from 15 submissions and are complemented with an invited talk. The papers discuss recent advances in the field of computational morphology.